ANALISIS SAFETY FACTOR LERENG DENGAN PERKUATAN CORRUGATED CONCRETE SHEET PILE BOZEM KALIDAMI SURABAYA - Indra Wahyu Utomo; Laily Endah Fatmawati (LPPM Universitas Abdurrab, 2024)
In the field of geotechnical engineering, one of the most common causes of landslides is an increase in shear stress in the soil or a decrease in the shear strength of the soil mass so that it cannot withstand the applied load. Analysis of the slopes of Bozem Kalidami Surabaya was carried out to determine the safety figures for slopes reinforced with sheet pile retaining walls based on data obtained from boring tests. The sheet pile used is CCSP Type W-600 class B 19 meters long. Analysis of safety figures is carried out in two ways, namely manual calculation using the Fellinius method and the Plaxis v.8.2 program which aims to compare the results. Analyzed using manual calculations using the Fellenius method, the security value was 1.634. Meanwhile, for the results of the Plaxis v.8.2 program, the security value was 1.891. Because the calculation results obtained from both methods are >1.5, it can be concluded that the stability of the Bozem Kalidami Surabaya slope with CCSP Type W-600 class B reinforcement with a length of 19 meters is safety.